2014 International Conference on Electrical Machines (ICEM) 2014
DOI: 10.1109/icelmach.2014.6960391
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic testing characterization of a HEV traction motor

Abstract: The dynamic testing method, as an alternative to traditional bench testing against a brake, has proven to be a fast, convenient, yet accurate way of characterizing electrical machines. By measuring the speed and the currents and voltages while alternatively accelerating and decelerating the electrical machine it is possible to obtain its torque and flux linkage characteristics dynamically.This article presents the application of the dynamic testing method to the validation of a HEV electric traction machine, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…To solve this problem in [19] a dynamic test method of electrical machines is proposed as an alternative to the traditional test bench where a torque sensor is required. It is shown that, with the measurement of velocity, current, and voltage, while accelerating and decelerating an electric motor, it is possible to dynamically estimate the torque and the characteristics of the flux linkage.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem in [19] a dynamic test method of electrical machines is proposed as an alternative to the traditional test bench where a torque sensor is required. It is shown that, with the measurement of velocity, current, and voltage, while accelerating and decelerating an electric motor, it is possible to dynamically estimate the torque and the characteristics of the flux linkage.…”
Section: Introductionmentioning
confidence: 99%